Comprehensive approach of methods for microstructural analysis and analytical tools in lignocellulosic biomass assessment – A review - Rodrigues, Rita C.L.B.; Green Rodrigues, Bruna; Vieira Canettieri, Eliana [UNESP]; Acosta Martinez, Ernesto; Palladino, Fernanda; Wisniewski Jr, Alberto; Rodrigues Jr, Durval (Elsevier, 2022)
The trend in the modern world is to replace fossil fuels with green energy sources in order to reduce their environmental impact. The biorefinery industry, within this premise, needs to establish quantitative and qualitative analytical methods to better understand lignocellulosic biomass composition and structure. This paper presents chemical techniques (chromatography, thermal analysis, HRMS, FTIR, NIR, and NMR) and physicochemical techniques (XRD, optical and electron microscopy techniques – Confocal fluorescence, Raman, SPM, AFM, SEM, and TEM) for the microstructural characterization of lignocellulosic biomass and its derivatives. Each of these tools provides different and complementary information regarding molecular and microstructural composition of lignocellulosic biomass. Understanding these properties is essential for the design and operation of associated biomass conversion processing facilities. PAT, monitored in real-time, ensures an economical and balanced mass-energy process. This review aimed to help researchers select the most suitable analytical technique with which to investigate biomass feedstocks with recalcitrant natures.
Keywords: Biorefinery; Lignin; Process analytical technology; Recalcitrant feedstock; Renewable energy